Intestinal Leiomyositis: A Cause of Chronic Intestinal Pseudo‐Obstruction in 6 Dogs. (26th November 2015) - Zacuto, A.C.; Pesavento, P.A.; Hill, S.; McAlister, A.; Rosenthal, K.; Cherbinsky, O.; Marks, S.L.
Abstract : Background: Intestinal leiomyositis is a suspected autoimmune disorder affecting the muscularis propria layer of the gastrointestinal tract and is a cause of chronic intestinal pseudo‐obstruction in humans and animals. Objective: To characterize the clinical presentation, histopathologic features, and outcome of dogs with intestinal leiomyositis in an effort to optimize treatment and prognosis. Animals: Six client‐owned dogs. Methods: Retrospective case series. Medical records were reviewed to describe signalment, clinicopathologic and imaging findings, histopathologic diagnoses, treatment, and outcome. All biopsy specimens were reviewed by a board‐certified pathologist. Results: Median age of dogs was 5.4 years (range, 15 months–9 years). Consistent clinical signs included vomiting (6/6), regurgitation (2/6), and small bowel diarrhea (3/6). Median duration of clinical signs before presentation was 13 days (range, 5–150 days). Diagnostic imaging showed marked gastric distension with dilated small intestines in 4/6 dogs. Full‐thickness intestinal biopsies were obtained in all dogs by laparotomy. Histopathology of the stomach and intestines disclosed mononuclear inflammation, myofiber degeneration and necrosis, and fibrosis centered within the region of myofiber loss in the intestinal muscularis propria. All dogs received various combinations of immunomodulatory and prokinetic treatment, antimicrobial agents, antiemetics, and IV fluids, but none of the dogs showed a clinically relevant improvement with treatment. Median survival was 19 days after diagnosis (range, 3–270 days). Conclusions and Clinical Importance: Intestinal leiomyositis is a cause of intestinal pseudo‐obstruction and must be diagnosed by full‐thickness intestinal biopsy. This disease should be considered in dogs with acute and chronic vomiting, regurgitation, and small bowel diarrhea.